PERMOHONAN SITA MARITAL DALAM PEMBAGIAN HARTA BERSAMA PERSPEKTIF MAQASHID SYARIAH - Purnama Sari, Ratih; Huzaimah, Arne; Ars Himsyah, Fatroyah (Usroh, 2024)
Joint property is one of the important aspects of the marriage relationship regulated in Islamic law and positive law in Indonesia. In practice, the division of joint property often becomes a problem that triggers conflict during divorce. One of the legal instruments available to protect joint property is the application for marital confiscation, which is a legal action to secure property so that it is not misused by one of the parties during the divorce process. This study aims to analyze the provisions of marital confiscation against joint property claims and analyze the Maqashid Sharia perspective on the provisions of marital confiscation of joint property claims. The research method used is library research with a normative juridical research approach. The data analysis technique used is descriptive analysis which uses deductive thinking flow. The results of this study indicate that marital confiscation has an important role in maintaining justice and protecting the rights of joint assets in the division of joint property, and has provisions regulated in various laws and regulations. Marital confiscation arrangements can be found in several laws and regulations, including Article 190 of the Civil Code, Article 24 paragraph (2) letter c of Government Regulation No. 9 of 1975, Article 78 letter c of Law No. 7 of 1989 jo. Law No. 3 of 2006, and Article 823 Rv. According to the Maqashid Sharia perspective, the provision of marital confiscation against joint property claims can be interpreted as an effort to preserve joint property, offspring, soul, religion, and reason. This is in accordance with the principles of Maqashid Sharia which prioritizes the benefit of mankind in various aspects of life, including in the context of divorce.